KEEFEKTIFAN PEMBELAJARAN BAHASA INDONESIA MELALUI GOOGLE CLASSROOM DI MASA PANDEMI - Layla Lusia Ningrum; Suparmin Suparmin; Titik Sudiatmi; Ita Retnowati (Kantor Bahasa Kalimantan Timur, 2021)
During the covid 19 pandemic, all students ranging from elementary school to student level are required to do learning through online. This policy provided by the Ministry of Education is intended to keep students learning safely at home in the midst of the Covid-19 pandemic and to ensure students continue to receive lessons during the pandemic. One application that is widely used during online learning today is google classroom. the author wants to research the effectiveness of Indonesian language learning through google classroom during the pandemic. If viewed through data, it can be concluded that there is an increase in student attendance and learning outcomes. With this can also be concluded that online learning through google classroom has effectiveness and can be used as an alternative learning during the pandemic.